Mind-stimulating leisure activities: Prospective associations with health, wellbeing, and longevity - Weziak-Bialowolska, Dorota; Bialowolski, Piotr; Sacco, Pier Luigi (Frontiers in Public Health, 2023)
This study examines prospective associations within a 6-year perspective between three mind-stimulating leisure activities (relaxed and solitary: reading; serious and solitary: doing number and word games; serious and social: playing cards and games) and 21 outcomes in (1) physical health, (2) well-being, (3) daily life functioning, (4) cognitive impairment, and (5) longevity domains. Data were obtained from 19,821 middle-aged and older adults from 15 countries participating in the Survey of Health, Aging, and Retirement in Europe (SHARE). Temporal associations were obtained using generalized estimating equations. All models were controlled for prior sociodemographic, personality, lifestyle factors, health behaviors, and pre-baseline leisure activity values and all outcome variables. The Bonferroni correction was used to correct for multiple testing. E-values were calculated to examine the sensitivity of the associations to unmeasured confounding. Secondary analyses (1) under the complete case scenario, (2) after excluding respondents with health conditions, and (3) using a limited set of covariates were conducted to provide evidence of the robustness of the results. The relaxed solitary activity of reading almost daily was prospectively associated with a lower risk of depression, experiencing pain, daily functioning limitations, cognitive impairment, lower loneliness scores, and more favorable well-being outcomes. Engaging in serious solitary leisure activities almost daily was prospectively associated with a lower risk of depression, feeling full of energy, and a lower risk of death by any cause. Occasionally engaging in these activities was prospectively associated with greater optimism and a lower risk of cognitive impairment. Engaging in serious social activities was prospectively associated with greater happiness, lower scores on the loneliness scale, a lower risk of Alzheimer’s disease, and an increased risk of cancer. Additionally, occasionally engaging in serious social activities was associated with greater optimism and lower risk of depression, pain, and mobility limitations. These associations were independent of demographics, socioeconomic status, personality, history of diseases, and prior lifestyle. The sensitivity analyses provided substantial evidence for the robustness of these associations. Mind-engaging leisure activities can be considered a health and well-being resource. Practitioners may consider them tools that help middle-aged and older adults maintain their health and quality of life.